Video Enhancement Using Adaptive Spatio-Temporal Connective Filter and Piecewise Mapping. (4th June 2008) - Wang Wang, Chao Chao; Sun Sun, Li-Feng Li-Feng; Yang Yang, Bo Bo; liu liu, Yi-Ming Yi-Ming; Yang Yang, Shi-Qiang Shi-Qiang
Abstract : This paper presents a novel video enhancement system based on an adaptive spatio-temporal connective (ASTC) noise filter and an adaptive piecewise mapping function (APMF). For ill-exposed videos or those with much noise, we first introduce a novel local image statistic to identify impulse noise pixels, and then incorporate it into the classical bilateral filter to form ASTC, aiming to reduce the mixture of the most two common types of noises—Gaussian and impulse noises in spatial and temporal directions. After noise removal, we enhance the video contrast with APMF based on the statistical information of frame segmentation results. The experiment results demonstrate that, for diverse low-quality videos corrupted by mixed noise, underexposure, overexposure, or any mixture of the above, the proposed system can automatically produce satisfactory results.